Effects of a Mindfulness-Based Parental Reflection Intervention on Pregnancy-Related Distress: A Pilot Study - Lucia Ciciolla; Samantha Addante; Karina M. Shreffler; Julie M. Croff (Mary Ann Liebert, 2023)
Background: Mindfulness-based interventions have been shown to be efficacious for reducing psychological distress and mental health symptoms and promoting well-being, including during pregnancy and postpartum. There is promising, though limited, evidence showing that interventions that focus on improving the mother-infant relationship are associated with improvements in both the mother-infant relationship and maternal mental health symptoms. The current study examines the effects of a prenatal mindfulness-based, reflective intervention designed to enhance maternal-fetal bonding on pregnancy-related distress and prenatal depressive symptoms. Methods: Out of a larger sample of 130 pregnant women in their second trimester, 15 women were recruited to participate in a 2-week long mindfulness-based, reflective intervention with daily short (<5-minute) activities. Multiple linear regression analyses were conducted to examine associations between the intervention and pregnancy-related distress and depression during the third trimester of pregnancy, controlling for race, age, education, union status, and first trimester depressive symptoms. Results: Results indicate that women who participated in the intervention during their second trimester reported lower pregnancy-related distress in their third trimester but no differences in depressive symptoms. Conclusions: A brief, mindfulness-based intervention delivered during pregnancy via cellphone texts can be a useful tool to reduce maternal distress related to pregnancy. Additional reflective exercises that address mood and global stress, as well as increasing the amount and/or frequency of the intervention, may be important for promoting maternal mental health more globally.